2009
DOI: 10.1007/s00705-009-0398-5
|View full text |Cite
|
Sign up to set email alerts
|

Hytrosaviridae: a proposal for classification and nomenclature of a new insect virus family

Abstract: Salivary gland hypertrophy viruses (SGHVs) have been identified from different dipteran species, such as the tsetse fly Glossina pallidipes (GpSGHV), the housefly Musca domestica (MdSGHV) and the narcissus bulbfly Merodon equestris (MeSGHV). These viruses share the following characteristics: (i) they produce non-occluded, enveloped, rod-shaped virions that measure 500-1,000 nm in length and 50-100 nm in diameter; (ii) they possess a large circular double-stranded DNA (dsDNA) genome ranging in size from 120 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…The GpSGHV outgroup, despite the fact that it was the taxon most closely related to MdSGHV (1,5), was present on a branch that was at least 3 orders of magnitude longer than the branches between the MdSGHV isolates, which were extremely short. Whereas the sequence-level and syntenic differences between these two members of the Hytrosaviridae have been described well elsewhere (5), we observed that the level of sequence identity for MdSGHV geographic isolates was high.…”
Section: Resultsmentioning
confidence: 93%
“…The GpSGHV outgroup, despite the fact that it was the taxon most closely related to MdSGHV (1,5), was present on a branch that was at least 3 orders of magnitude longer than the branches between the MdSGHV isolates, which were extremely short. Whereas the sequence-level and syntenic differences between these two members of the Hytrosaviridae have been described well elsewhere (5), we observed that the level of sequence identity for MdSGHV geographic isolates was high.…”
Section: Resultsmentioning
confidence: 93%
“…Finally, two large DNA viruses causing salivary gland hypertrophy of the tsetse fly Glossina pallidipes (GpSGHV) and the housefly Musca domestica (MdSGHV) were shown to share at least eight homologues of baculovirus core genes [12,13]. Despite some structural, biological, and genomic similarities with baculoviruses and nudiviruses, single gene trees based on DNA polymerase sequences as well as alignment-free proteome phylogenies implicated an association of SGHVs with vertebrate herpesviruses [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Musca domestica salivary gland hypertrophy virus (MdSGHV) is one of three known members of the newly described virus family Hytrosaviridae; the other two viruses infect adult tsetse (Glossinidae) and narcissus bulb ßies (Syrphidae) (Abd-Alla et al 2009). MdSGHV has been found in house ßy populations globally, generally at fairly low prevalence rates (Geden et al 2008, Prompiboon et al 2010.…”
mentioning
confidence: 99%